2013
DOI: 10.5114/pg.2013.39920
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of autoantibodies for gastrointestinal autoimmune diseases in children with common variable immune deficiency and selected IgA deficiency

Abstract: IntroductionSelected IgA deficiency (IgAD) and common variable immune deficiency (CVID) are humoral immunity deficiencies frequent in children. In both these types of immunodeficiency, autoimmune diseases are present in 20–30% of patients, but the disease profiles are different between adults and children. Autoimmune diseases of the gastrointestinal tract (IBD) and celiac disease are typical for children with IgAD and CVID. Diagnosis is based on clinical symptoms, histology of jejunum and antibodies often prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In our study, there was an association between a defect in specific antibody responses and negative results in related serologic test in patients with rheumatologic complications. Pituch‐Noworolska et al in 2013 evaluated autoantibodies in children with CVID and report that antibodies are produced despite impaired humoral immunity, but their level might be lower than immunocompetent individuals affected by autoimmunity. In another study, Milota et al described 2 patients with a combination of T1D and CVID with serious impairment of antibody production.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, there was an association between a defect in specific antibody responses and negative results in related serologic test in patients with rheumatologic complications. Pituch‐Noworolska et al in 2013 evaluated autoantibodies in children with CVID and report that antibodies are produced despite impaired humoral immunity, but their level might be lower than immunocompetent individuals affected by autoimmunity. In another study, Milota et al described 2 patients with a combination of T1D and CVID with serious impairment of antibody production.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in IgAD patients with coeliac disease, the production of anti‐EMA, AGA and AtTGA are preserved, but only in the IgG class. However, in some IgAD patients, despite the lack of IgA in serum, the presence and high levels of AtTGA have been reported in the IgA class .…”
Section: Management Of Autoimmunity In Pid Patientsmentioning
confidence: 99%
“…An association between certain antibodies and the pathogenesis of autoimmune GI diseases has been established. For many years, the serologic diagnosis of coeliac disease was based on the detection of IgA anti‐endomysial antibodies (EMA), IgA and IgG antigliadin antibodies (AGA), and antitissue transglutaminase antibodies (AtTGA) as well as IgA antireticulin antibodies . It has been demonstrated that the levels of these autoantibodies in the serum of PID patients are often lower than in patients without PID .…”
Section: Management Of Autoimmunity In Pid Patientsmentioning
confidence: 99%
“…It is well known that these diseases may share a common dysregulation of the ICOS molecule [ 65 ], and coexistence in the same family of patients with CD and CVID has been described [ 66 ]. Although celiac-like lesions can be observed in 30% of CVID patients, the true prevalence of CD in CVID is much lower, as reported in Table 3 [ 41 , 63 , 67 , 68 , 69 , 70 ], being 9.2% overall. Biagi et al [ 70 ] have observed that the histologic response to a GFD is the only reliable tool to establish the diagnosis of CD in CVID.…”
Section: Immunoglobulin Deficiencies and Celiac Diseasementioning
confidence: 99%
“…The prevalence of CD in sIgAD is much more than in the general population, ranging from 6.7%–20.6% as summarized in Table 2 [ 38 , 39 , 40 , 41 , 42 , 43 ]. On the other hand, sIgAD is more common in celiac patients, with a prevalence of 1:39 [ 44 ].…”
Section: Immunoglobulin Deficiencies and Celiac Diseasementioning
confidence: 99%